The P2X7 Receptor in Tumor Immunity - Grassi, Fabio; De Ponte Conti, Benedetta (Frontiers in Cell and Developmental Biology, 2021)
Extracellular adenosine triphosphate (eATP) is a potent mediator of the immune response via stimulation of purinergic P2 receptors. ATP concentration in the extracellular space increases dramatically during tissue damage and eATP acts as a danger-associated molecular pattern (DAMP) to alert innate immune system cells for tissue repair. Similarly, eATP is present at hundreds of micromolar concentration in the tumor microenvironment (TME). However, its impact on antitumor immune response is still not well established, probably because of the complexity of the responses it induces in different cells constituting the TME. On one hand, ATP released by tumor cells concomitantly to cell death can contribute to immunogenic cell death (ICD) that is proinflammatory for the innate immune compartment and beneficial for tumor control, while on the other hand, eATP can foster immune-suppressive mechanisms within the TME, thus contributing to tumor progression and metastasis. It is well established that T-cell immunity is pivotal in limiting tumor growth and possibly eradicating neoplastic cells. T cells are limited though in their antitumor activity through different mechanisms, such as exhaustion, anergy, and senescence; the pathways resulting in these cellular outcomes are not clear. Here, we review the function of P2X7 receptor in conditioning T cell-dependent immunity against cancer.